Contribution of urease to acid tolerance in Yersinia enterocolitica. - De Koning-Ward, T F (1995)
The stomach serves as a barrier to enteric infection because of the antibacterial effect of the hydrochloric acid in gastric juice. In this study, we tested the ability of the enteric pathogen Yersinia enterocolitica to tolerate a pH range of 2.0 to 6.0 and found that under the conditions of a normal human fasting stomach (pH < 3 and a gastric emptying time of 2 h), Y. enterocolitica is highly acid resistant, showing approximately 85% survival. The resistance of Y. enterocolitica to acid in vitro depended on the bacterial growth phase and the concentration of urea in the medium, being maximal during stationary phase in the presence of at least 0.3 mM urea. Urease-negative mutants of Y. enterocolitica were constructed by disrupting the urease gene complex of a virulent strain of serogroup O9. Compared with the wild type, these mutants showed an approximately 1,000-fold decrease in the ability to tolerate acid in vitro (< 0.08% survival) and a 10-fold reduction in viability after passage through the stomachs of mice. Complementation of the disrupted urease genes in trans restored the ability of urease-negative mutants to tolerate low pH in vitro and gastric acidity to approximately wild-type levels. These findings indicate that urease is responsible for acid resistance in Y. enterocolitica and suggest that urease contributes to the virulence of Y. enterocolitica by enhancing the likelihood of bacterial survival during passage through the stomach.